Edukasi Tentang Pencegahan Infeksi Kecacingan Disebabkan Oleh Soil Transmitted Helmith Dengan Menggunakan Metode Ceramah Kepada Masyarakat Di Desa Namo Rambe - Joice Sonya Panjaitan (Jurnal Visi Pengabdian Kepada Masyarakat, 2022)
Soil Transmitted Helminth, also known as intestinal worm infection, is the most common worm disease caused by Ascaris lumbricoides, Trichuris trichiura, Strongyloides stercoralis, Necator americanus and Ancylostoma sp. The purpose of this activity is to find out the incidence of worms, provide education and treat worms obtained in Namo Rambe Village. The activity method of this activity is the general lecture. This counseling was considered quite successful as seen from the questionnaires answered by the participants about the clinical symptoms of worms. It can be concluded that this outreach activity is very useful in increasing knowledge and community participation in preventing helminth infections. Keywords: helminth infection, Soil Transmitted Helmith, prevention, counseling, Namo Rambe village